SUSTAINABLE HOUSING: A CONCEPTUAL APPROACH - Celiker, Afet (Open House Int, 2017)
Sustainable architecture is a well-known and studied subject for severeal decades. The environmental awareness of professionals has put sustainability in the center of the profession of architecture and has resulted in introducing and implementing ecological designs both in the scale of buildings and cities. This article presents sustainable architecture criteria, reckons regional aspects, interprets vernacular architecture and, proposes sustainable housing unit models for Mediterranean region, specifically Cyprus. The article intends to study existing researches regarding the subject, reveals and updates key aspects on sustainable housing by focusing on the passive solar systems through proposals. The article contains proposals of an experimental and conceptual approach of a group of graduate studio course students who are architects and interior designers. The conceptual approaches of design proposals are sustainable through the usage of local materials, orientation, usage of passive solar systems, natural ventilation and lighting, hence these proposals are intended to create a diversity. In that sense, this article presents possibilities of ideal plan layouts and facades for sustainable architectural housing units in Mediterranean region, Cyprus, based on the revealed key aspects on sustainability. The originality of the article is on the design proposals that take inspiration from the characteristics of vernacular architecture, but show a contemporary approach of design.
Keywords: Sustainable Architecture; Housing; Environment; Design; Cyprus